Isoniazid acetylating phenotype in patients with paracoccidioidomycosis and its relationship with serum sulfadoxin levels, glucose-6-phosphate dehydrogenase and glutathione reductase activities - Barraviera, Benedito [UNESP] (1991)
The authors evaluated the isoniazid acetylating phenotype and measured hematocrit, hemoglobin, glucose-6-phosphate dehydrogenase and glutathione reductase activities plus serum sulfadoxin levels in 39 patients with paracoccidioidomycosis (33 males and 6 females) aged 17 to 58 years. Twenty one (53.84%) of the patients presented a slow acetylating phenotype and 18 (46.16%) a fast acetylating phenotype. Glucose-6-phosphate-dehydrogenase (G6PD) activity was decreased in 5(23.80%) slow acetylators and in 4 (22.22%) fast acetylators. Glutathione reductase activity was decreased in 14 (66.66%) slow acetylators and in 12(66.66%) fast acetylators. Serum levels of free and total sulfadoxin were higher in slow acetylator (p _ 0.02). Analysis of the results permitted us to conclude that serum sulfadoxin levels are related to the acetylator phenotype. Furthermore, sulfadoxin levels were always above 50 μg/ml, a value considered therapeutic. Glutathione reductase deficiency observed in 66% of patients may be related to the intestinal malabsorption of nutrients, among them riboflavin, a FAD precursor vitamin, in patients with paracoceidioidomycosis.